Autoimmunity and genetics contribute to the risk of insulin-dependent diabetes mellitus in families: islet cell antibodies and HLA DQ heterodimers - Lipton, R B; Kocova, M; LaPorte, R E; Dorman, J S; Orchard, T J; Riley, W J; Drash, A L; Becker, D J; Trucco, M (Oxford Academic, 1992)
The risk for insulin-dependent diabetes mellitus (IDDM) associated with genetic susceptibility markers at the human leukocyte antigen (HLA) DQA1 and DQB1 loci was evaluated among individuals with and those without islet cell antibodies. A total of 108 antibody-positive parents and siblings of IDDM patients from the Pittsburgh registry were identified among 1,592 who were screened. HLA-DQ molecular typing was performed on 79 of these individuals and on 78 antibody-negative relatives. There were similar proportions of homozygotes for both of the diabetogenic alleles DQA1 arginine-52 (R/R) and DQB1 non-aspartate-57 (nD/nD) among the antibody-positive and antibody-negative relatives (19.0 and 15.4%, respectively). However, subsequent development of IDDM was restricted to individuals who were both antibody positive and carried the potential to make at least one diabetogenic DQ heterodimer. A dose-response effect was observed among the antibody-positive relatives, in which two of 18 capable of generating one diabetogenic heterodimer and six of 29 generating two heterodimers became insulin requiring. Nine of 15 who were homozygous for both R/R and nD/nD, coding exclusively for diabetogenic variants, became diabetic over the course of the follow-up. With a multivariate model, the relative risk for IDDM among those with islet cell antibodies who were also R/R and nD/nD was estimated to be 229.3 compared with those lacking both, after age and sex were controlled for. The data suggest that while autoimmunity, indicated by the presence of cytoplasmic islet cell antibodies may be relatively common, it progresses only in those with variant HLA-DQ molecules.